Answer:
Here
Step-by-step explanation:
Irrational exponents are non repeating or infinite decimals while rational exponents are rational numbers. The value of an irrational exponent when calculated is approximate in nature while the value of rational exponent is exact.
Answer:
8:00am I'm not sure, sorry if I get it wrong dude...
The terms
and
can be added to
to result in a monomial.
Step-by-step explanation:
Given term is;
![3x^2y](https://tex.z-dn.net/?f=3x%5E2y)
A monomial is an algebraic expression that consists of only one term.
So in the given expressions, we will add the terms which have same variables as given terms.
Given options are;
![3xy\\-12x^2y\\2x^2y^2\\7xy^2\\-10x^2\\4x^2y\\3x^3](https://tex.z-dn.net/?f=3xy%5C%5C-12x%5E2y%5C%5C2x%5E2y%5E2%5C%5C7xy%5E2%5C%5C-10x%5E2%5C%5C4x%5E2y%5C%5C3x%5E3)
The terms
and
can be added to
to result in a monomial.
The equations would be
<span>Value: b + c = 19000
Interest: 0.07b + 0.09c = 1590
</span>0.07b + 0.09 (19,000 - b) = 1,590
0.07b + 1,710 - .09b = 1,590
<span>120 = .02b
</span>
B = 6,000
<span>C = 13,000
</span><span>
So the correct answer is </span><span>d. $6000 in bonds; $13,000 in certificates of deposit.
</span>
Thank you for posting your question. I hope that this answer helped you. Let me know if you need more help.
(√3 + √11)² + (√3 - √11)²
- (a+b)² = a² + b² + 2ab
- ( a - b )² = a² + b² - 2ab
<em>Now </em><em>,</em>
(√3 + √11)² + (√3 - √11)²
(3 + 11 + 2√3√11)+ (3 +11 - 2√3√11)
14 + 2√33+ 14 - 2√33
14 + 14 = 28
Hence , The value of (√3 + √11)² + (√3 - √11)² is 28 .